Modern Diplomacy and the Changing Nature of International Politics in the 21st Century - Marc E. Oosthuizen (Journal of BRICS Studies)
International politics have become more complex since the end of the Cold War in the late 1980s, and consequently, it confuses traditional diplomats.[i] This intricacy is because the post-Cold War international era requires diplomacy to move from being foremost about high politics such as security, military and geopolitical issues to incorporating a wider and growing scope of issues outside of a state’s national borders like migration, gender, global warming, desertification and diseases. Not only are these novel policy themes an indication of how diplomacy’s agenda is growing, but they also indicate that an increasing number of participating stakeholders must be included in contemporary diplomatic practice.[ii] To further scrutinise the phenomena driving change and influencing modern diplomacy, the research utilises specific and relevant international political issues such as post-Cold War international politics, the hegemonic decline of the US, the rise of China, the problems in the Middle East, nuclear disarmament, climate change, Globalisation, the Fourth Industrial Revolution (4IR), the COVID-19 pandemic and diplomatic inflation.